Genome-wide association and RNA-seq analyses reveal genes linked to salt stress in peanut (Arachis hypogaea L.) - Zou, Kunyan; Kang, Yang Jae; Ha, Bo-Keun; Kim, Kyung Do; Kim, Ki-Seung; Jun, Tae-Hwan (Frontiers in Plant Science, 2025)
Salt stress adversely affects seed germination, seedling growth, and development, considerably impacting peanut (Arachis hypogaea L.) production. However, their genetic and genomic responses to salinity remain poorly understood. To identify candidate genes associated with salt tolerance, a genome-wide association study (GWAS) of 295 peanut genotypes and RNA sequencing (RNA-seq) analysis of two contrasting accessions (tolerant and susceptible) exposed to 200 mM NaCl at the seedling stage were conducted. Leaf scorch, sodium ion concentration, proline content, and chlorophyll content were evaluated as primary indicators of salt tolerance. GWAS identified 10 single-nucleotide polymorphisms significantly associated with salt stress. Transcriptome analysis of root tissues revealed 1,734 differentially expressed genes, significantly enriched in pathways such as oxidoreductase activity, defense response, flavonoid biosynthesis, transcription factor activity, and cytochrome P450-related functions. Seventeen common candidate genes were identified through the integration of GWAS and RNA-seq results. Of these genes, seven exhibited expression levels significantly correlated with relevant salt tolerance traits. Sequence variations were detected in two of the seven genes, associated with sodium ion content and leaf scorch score, respectively. Using validated mutation data, we developed a kompetitive allele-specific polymerase chain reaction marker to assess proline levels, which enable breeders to make precise and early selections at the field level, thereby reducing both the time and cost required for developing new salt-tolerant varieties through efficient marker-assisted selection. Our integrated genomic and transcriptomic analysis identified seven high-confidence candidate genes, providing new insights and theoretical basis for cloning salt-tolerant genes. These findings advance understanding of the molecular mechanisms underlying peanut adaptation to salt stress and offer valuable genetic resources, including tolerant accessions and associated or linked genomic regions, to support breeding programs for developing salt-tolerant cultivars.